Regulation of transport activities taking into account the requirements of European standards - Volik, Viacheslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article deals with issues related to the operation and operation of automobile carriers in Ukraine and points to the need to bring existing legislation in line with the European one. The current state of legal regulation of this stratum of relations in society is analyzed. The proposal to improve the quality of organization and operation of automobile carriers with the promotion of the European level of quality of work is proposed